Reforming SADC’s legal framework for cross-border public-private partnership to enhance infrastructure delivery - Basimanyane, Dorcas K. (University of Pretoria, 2025)
Mini Dissertation (LLM (International Trade and Investment Law in Africa))--University of Pretoria, 2025.